Developing technical training : a structured approach for developing classroom and computer-based instructional materials - Clark, Ruth Colvin; Clark, Ruth Colvin (Hoboken, New Jersey : John Wiley & Son, Inc., 2008)
Since it was first published almost twenty years ago, Developing Technical Training has been a reliable resource for both new and seasoned training specialists. The third edition of this classic book outlines a systematic approach called the Instructional Systems Design (ISD) process that shows how to teach technical content defined as facts, concepts, processes, procedures, and principles. Whether you teach "hard" or "soft" skills, or design lessons for workbooks or computers, you will find the best training methods in this book.
About This Book; Why Is Developing Technical Training Important?; What's New in the Third Edition?; What Can You Achieve with This Book?; How Is This Book Organized?; About Pfeiffer; Dedication; Title Page; Copyright Page; Acknowledgments; Introduction; Purpose; Audience; Package Components; SECTION 1 -- An Introduction to the Technology of Training; Chapter 1: The Technology of Training; Chapter 2: An Introduction to Structured Lesson Design; Chapter 1 -- The Technology of Training; The Costs of Training Waste; Why We Can't Afford Ineffective Technical Training; What Is Technical Training? Instructional Systems Design: An OverviewIs ISD Dead?; The Four Ingredients of Instruction; Which Instructional Media Are the Best?; Time for ISD; Check Your Understanding; An Introduction to Structured Lesson Design; For More Information; Chapter 2 -- An Introduction to Structured Lesson Design; The Anatomy of a Lesson; Communication Modes in Training; Communication Guidelines for Instructor-Led Training; Communication Guidelines for Asynchronous e-Learning; Educational Taxonomies and Instructional Methods; An Overview of the Content-Performance Matrix. Instructional Methods Matched to Content TypesFor More Information; SECTION 2 -- How to Teach Facts, Concepts, Processes, Procedures, and Principles; Chapter 3: How to Teach Procedures; Chapter 4: How to Teach Concepts; Chapter 5: How to Teach Facts; Chapter 6: How to Teach Processes; Chapter 7: How to Teach Principles; Chapter 3 -- How to Teach Procedures; What Is a Procedure?; Check Your Understanding; Learning Procedures at the Remember and Application Levels; Writing Procedure Learning Objectives at the Application Level; Training Procedures; Teaching Procedures in the Classroom. Teaching Procedures in e-LearningPractice Methods for Procedures; Performance Support for Procedures; Evaluating Learning of Procedures; How to Teach Supporting Knowledge; For More Information; Chapter 4 -- How to Teach Concepts; What Is a Concept?; Check Your Understanding; Learning Concepts at the Remember and Application Levels; Writing Concept Learning Objectives at the Application Level; Training Concepts; Teaching Concepts in the Classroom; Teaching Concepts in e-Learning; Practice Methods for Concepts; Evaluating Learning of Concepts; How to Teach Facts; Chapter 5 -- How to Teach Facts. What Is Factual Information?Check Your Understanding; Learning Facts at the Remember Level; Writing Learning Objectives for Factual Information; Training Facts; Training Facts in the Classroom; Use Statements for Associative Facts; Teaching Factual Information in e-Learning; Reference-Based Training; Use Inductive Learning to Engage Learners with Facts; Practice Methods for Facts; Evaluating Learning of Facts; How to Teach Process Content; For More Information; Chapter 6 -- How to Teach Processes; What Is a Process?; Check Your Understanding.
Includes bibliographical references and index.
Keywords: TECHNOLOGY -- STUDY AND TEACHING